Implementation of Group Activity-Based Learning Strategies in Islamic Religious Education to Enhance Student Engagement - Duhita, Valda Ratna; Rohman, Fathur (Universitas Islam Sultan Agung, 2025)
This study aims to describe the implementation of group activity-based Islamic Religious Education learning in enhancing student engagement, which includes active participation in discussions, collaboration among students, and students’ involvement in expressing opinions during the learning process. Data were collected at SMA Negeri 1 Bangsri through observations, in-depth interviews, and document analysis. The research subjects consisted of Islamic Religious Education teachers and tenth-grade students involved in group activity-based learning. The results indicate that the implementation of group activity-based Islamic Religious Education learning through discussions and presentations significantly increases student engagement, as reflected in higher levels of active participation, collaboration among students, and confidence in expressing opinions. Teachers play a role as facilitators who guide discussions and ensure the involvement of all group members. These findings imply that group activity-based learning strategies are able to create a more interactive and meaningful learning environment in Islamic Religious Education, although their implementation still faces challenges such as time limitations and unequal distribution of group tasks.